2019
DOI: 10.1080/17496535.2019.1598458
|View full text |Cite
|
Sign up to set email alerts
|

Doing Knowing Ethically – Where Social Work Values Meet Critical Realism

Abstract: This article focuses on the injustices experienced by already marginalised groups when they are excluded from participation in society, specifically within the realms of knowledge production and transfer. In this sense they are wronged as 'knowers' and experience epistemic injustice, either as a consequence of perceived credibility deficits or due to a lack of understanding of their situation. As a result, their marginalisation and exclusion grows.This article argues that a values orientation of acceptance, aw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…SARs describe what is found but rarely penetrate beneath the surface of what has been observed (Dore, 2019) with analytic depth to answer questions "why?" In setting terms of reference and in their quality assurance of reports, SABs should ensure that reviews have analysed what promoted and sustained good practice, where it was found and what human and organisational factors obstructed best practice.…”
Section: P3mentioning
confidence: 99%
See 1 more Smart Citation
“…SARs describe what is found but rarely penetrate beneath the surface of what has been observed (Dore, 2019) with analytic depth to answer questions "why?" In setting terms of reference and in their quality assurance of reports, SABs should ensure that reviews have analysed what promoted and sustained good practice, where it was found and what human and organisational factors obstructed best practice.…”
Section: P3mentioning
confidence: 99%
“…Recommendations for change accept current organisational structures as fixed and unchallengeable (Weiss, 1993). The orientation is reformist rather than a forensic examination of what sustains the observed findings (Dore, 2019). The focus is a change in a system rather than changing the system (Yu, 2015).…”
Section: P3mentioning
confidence: 99%